Comparison of 9.0 and 9.2 mm Flap Diameter Options of Femtosecond Laser In-Situ Keratomileusis for Hypermetropia and Hypermetropic Astigmatism - Kemal Ozulken; Cagri Ilhan (Journal of Ophthalmology)
Aim. To compare the postoperative one-year outcomes of asphericity (Q) and high order aberration (HOA) values of 9.0 and 9.2 mm diameter flap groups in hypermetropia and hypermetropic astigmatism subjects who underwent femtosecond laser in-situ keratomileusis (LASIK). Materials and Methods. The study included 68 eyes of 34 patients. A femtosecond laser platform (Allegrato Wave, Wavelight AG, Erlangen, Germany) was used for flap cutting. Corneal stroma was ablated using Wavelight EX500 with wavefront-optimized profile (WaveLight GmbH, Erlangen, Germany). 9.0 mm flap diameter was randomly chosen for one eye, and 9.2 mm flap diameter was chosen for the fellow eye. Two eyes of the patients who used two different flap diameters were enrolled into two different groups. Corneal stroma was ablated using Wavelight EX500 with wavefront-optimized profile (WaveLight GmbH, Erlangen, Germany). Postoperative one-year outcomes of Q and HOA values of 9.0 and 9.2 mm diameter flap groups were compared statistically. Results. The preoperative manifest refraction spherical equivalents of the 9.0 and 9.2 mm diameter flap groups were 1.86 ± 1.81 D and 1.69 ± 1.99 D (p=0.754). No intraoperative or postoperative complications were observed. At postoperative one-year, Q values were 0.98 ± 0.13 D and 0.91 ± 0.15 D (p=0.029). HOAs including horizontal and vertical coma, horizontal and vertical trefoil, spherical aberration, and second order vertical coma were not significantly different (p>0.05 for all). Total HOA values were 1.62 ± 0.14 and 1.40 ± 0.16, in the 9.0 and 9.2 mm diameter flap groups, respectively (p<0.001). Conclusion. Both the 9.0 and 9.2 mm diameter flap options in femtosecond LASIK are equally safe and effective. Many of the HOA values are similar in both options, and better results were provided in terms of total HOA and Q values with the 9.2 mm diameter flap option. This study was registered with trial registration number 118-011.